Sustained impact of rotavirus vaccine on rotavirus hospitalisations in Lusaka, Zambia, 2009–2016. Issue 47 (12th November 2018) - Mpabalwani, E.M.; Simwaka, J.C.; Mwenda, J.M.; Matapo, B.; Parashar, U.D.; Tate, J.E.
Abstract: Background: Monovalent rotavirus vaccine (RV1) was introduced in Lusaka in February 2012 and rolled out countrywide in November 2013 in the routine Expanded Programme on Immunisation and administered at 6 and 10 weeks with no catch up dose. Reported here is the monitoring of rotavirus acute gastroenteritis hospitalisations at the University Teaching Hospital, Lusaka, Zambia as part of efforts to document the impact of rotavirus vaccine. Methods: Children <5 years hospitalised for acute gastroenteritis (AGE) from January 2009 to December 2016 were recruited into the rotavirus disease burden active surveillance and had their stools tested for rotavirus by enzyme immunoassay. We compared rotavirus-associated AGE hospitalisations of the pre-vaccine era (2009–2011) with the post-rotavirus vaccine introduction period (2013–2016). Results: With the increase in RV1 coverage in Lusaka, rotavirus AGE declined significantly from 40% of diarrhoea hospitalisation in the pre-vaccine era to 29% of diarrhoea hospitalisation in the post-vaccine era (p < 0.001) in children <5 years. After a decreasing trend in rotavirus positivity from 2013 to 2015, positivity increased to 37% in 2016. However, the post-vaccine years (2012–2016) saw substantial decline in the number tested (median decline: 34% (range: 20–43%)) and the number of positive results (median decline: 52% (range: 30–65%). Conclusion: A sustained and significant decline in rotavirus AGE hospitalisations was observed in children <5 years since the introduction of RV1 in Lusaka, Zambia. Despite an increase in rotavirus positivity in 2016, the total number of children enrolled and the number of rotavirus positive children remained below baseline. The reason for the increase in rotavirus positivity in 2016 is unknown but could be due to an accumulation of susceptible children and the shifting of disease to children of older age groups. This finding underscores the need for continued monitoring of rotavirus vaccine impact.